Optimisation techniques for solar drying systems: a review on modelling, simulation, and financial assessment approaches - Kumar, Baibhaw; Szepesi, Gábor; Szamosi, Zoltán (International journal of sustainable energy, 2023)
The depletion of conventional energy resources has created a bunyanesque energy problem in the current world order. In this article, the byzantine issues of optimisation i.e. modelling, simulations, sustainability assessment and economic analysis examples are discussed briefly. Life span analysis and associated capital costs for various solar drying systems are elucidated with comparative graphics for insights into the economic benchmarking of different models. This compendium work highlights the suitable combinations of numerical modelling and simulation softwares frequently used. In addition, the recent studies on environmental assistance are reviewed which is a crucial parameter for future studies on solar dryer optimisation as they should not only limited to exergy-sustainability criteria but to expand the studies on social impact as well.